Wind-induced internal pressures on large cooling towers. Issue 15 (November 2019) - Cheng, XX; Wu, G; Zhao, L; Li, PF; Ge, YJ
Effects of wind-induced internal pressures on the cooling tower's structural performances are as significant as those of wind-induced external pressures. However, comparing to wind-induced external pressures, limited research focuses on wind pressures on the internal surfaces of large cooling towers. To fill up the scientific void, numerical analyses, physical model tests, and analytical studies are undertaken in this article. It is demonstrated that the draught ventilation ratio (i.e. the total area of the openings on the stuffing layer divided by the area of the stuffing layer) is the dominant factor for wind-induced internal pressures on large cooling towers, and 15% draught ventilation ratio can be regarded as the most unfavorable case. Besides, it is revealed that the theoretical formulation of the internal pressure on a single-cell building with a dominant opening and background porosity proposed by some other researchers can be applied to the case of a cooling tower subjected to strong winds. Using the validated theoretical formulation, the geometry of a large cooling tower is optimized with regard to the most favorable wind-induced internal pressure. The findings of this article are helpful for improving the current Chinese Code that governs the design of cooling towers.